Modulating electrolyte structure for ultralow temperature aqueous zinc batteries - Qiu Zhang (Nature Portfolio, 2020)
Rechargeable aqueous batteries are promising for potential large-scale energy storage due to their high safety and low cost. Here the authors analyse a zinc chloride based low-temperature electrolyte for improving practicability of the aqueous batteries.